0701 STOP-BANG Score, Age, and Body Mass Index Predict Severity of Sleep Disordered Breathing in Women Veterans. (25th May 2022) - Moghtaderi, Isabel; Kelly, Monica; Carlson, Gwendolyn; Fung, Constance; Josephson, Karen; Song, Yeonsu; Agrawal, Alpna; Zhu, Ruoyan; Mitchell, Michael; Badr, M Safwan; Washington, Donna; Yano, Elizabeth; et al.
Abstract: Introduction: Despite increasing evidence that sleep disordered breathing (SDB) is common in women veterans, little is known of how to screen for SDB in this population. Some evidence suggests there are sex-related differences in SDB presentation, where women may be more likely to present with fatigue or depression, compared to men who may present with daytime sleepiness. The goal of this study was to evaluate whether commonly used measures predict SDB in women veterans. Methods: Women veterans (N=179) without treated SDB, but with 1 or more SDB risk factors (identified from electronic medical records) completed baseline assessment as part of an ongoing controlled trial of treatment for SDB. Measures included: age, body mass index (BMI), Epworth Sleepiness Scale (ESS), Flinders Fatigue Scale (FSS), Insomnia Severity Index (ISI), Patient-Health Questionnaire 9-item (PHQ-9), STOP-BANG score, and apnea-hypopnea index (AHI via WatchPAT home sleep apnea testing). Descriptive statistics and bivariate correlations testing the relationship between AHI and other measures were performed. Results: Mean age was 49.8 [±13.8] years and BMI 29.6 [±6.0] kg/m2. Mean ESS was 8.1, FFS 13.9, ISI 14.0, PHQ-9 7.1, and STOP-BANG score 2.7. Mean AHI was 15.4 [±13.2], where higher AHI correlated with higher BMI (r=0.3, p<0.001), higher STOP-BANG score (r=0.4, p<0.001) and older age (r=0.4, p<0.001). Conclusion: These findings support the use of the STOP-BANG score to predict SDB severity in women veterans with risk factors for SDB. Age and BMI may be particularly important predictors of SDB in this population. Sleepiness, depression, insomnia, and fatigue questionnaires were not related to SDB severity. Further work is needed to understand the role of patient-reported symptoms in those at-risk for SDB and to inform guidelines for the recognition of SDB in this important and understudied population. Support (If Any): VA HSR&D IIR 16-244 and RCS 20-191; NIH/NHLBI K24 HL143055, HRS&D COIN; VAGLAHS GRECC.